Tafsir Surah al-Ikhlāṣ Berbasis Tartīb Nuzūlī: Studi Karya Tafsir M. Abid al-Jabiri - Salman Alfarisi (IAT dan ILHA, UIN KH ABDURRAHMAN WAHID, 2020)
This article tries to analyze the tafsir of surah al-IkhlÄá¹£ based on tartÄ«b nuzÅ«lÄ« in Muhammad Abid al-Jabiriâ€™s work, Fahm al-Qurâ€™a>n al-Haki>m: al-Tafsi>r al-Wa>dih Hasb Tarti>b al-Nuzu>l. Systematically, surah al-Ikhlas was put by al-Jabiri in the 19th order which entered into the theme of prophetic and deism. This surah is an affirmation of the Essence of God as well as the starting point for the transition of Godâ€™s terms: from ar-Rabb to Allah. This surah was also positioned as a response to the deism of Arab society who knew and believed in Allah, but they allied Him. Methodologically, al-Jabiriâ€™s work can be categorized as a tafsir with historical perspective (al-lawn at-tÄrikhÄ«). In term of interpretation sources, al-Jabiri doesnâ€™t limit himself to contemporary works, he also accomodates classical works. So that he is classified as an postmodernist commentator (mufassir). Through his work, al-Jabiri invites readers to think historically until they have a complete, holistic and comprehensive understanding of the verses of the Koran.",